Functional neuroimaging studies of aging and emotion: Fronto-amygdalar differences during emotional perception and episodic memory - ST JACQUES, PEGGY L. (2009)
Emotional processes are enhanced in aging, such that aging is characterized by superior emotional regulation. This article provides a brief review of the neural bases supporting this effect with a focus on functional neuroimaging studies of perception and episodic memory. The most consistent finding across these studies is that older adults show an alteration in the recruitment of the amygdala, but greater recruitment of the frontal cortex. These Fronto-amygdalar Age-related Differences in Emotion (FADE) may reflect emotional regulation strategies mediated by frontal brain regions that dampen emotion-related activations in the amygdala.